Analisis Kelayakan Pembukaan Toko Disneck Merchandise Dilihat Dari Aspek Pasar, Aspek Teknis, Aspek Keuangan, Dan Aspek Manajemen - Fauzan Fauzan; Budi Praptono; Nurdinintya Athari Supratman (eProceedings of Engineering, 2015)
ABSTRACT At the present time the need for individual people increasingly diverse, starting from basic needs, needs support to non-basic needs. Clothing is one of the basic needs that are essential in human survival. Large consumption rate becomes positive in the clothing industry, especially industrial development. The human need for clothing is growing into its own business opportunities for industry players. Merchandise Disneck is one of the local brand that sells items related to the world of fashion. At first, Diseneck Merchandise making sales through online media such as social media Twiiter, Faceebook, blackberry massager and buy-sell website. By looking at the number of sales of Disneck Merchandise which continues to grow from year 2010 - 2013 about 11.1% - 15.2% and to increase consumer trust to the brand of Diseneck Merchandise, Diseneck Merchandise planning to open its first store in Bandung city. Before making Disneck Merchandise Toko, feasibility analysis whether Disneck Merchandise Toko will make decent views of aspects of the market, aspects technical, financial aspects and management aspects. From the distribution of questionnaires, researchers get the percentage of the potential market is 96%, 92% and available market target market of 1.67%. for the financial aspects of investment expenditure and revenue estimates obtained by using the results of the analysis of the calculations have been done before. The period set for the financial projections is 5 years with MARR = 12%. Results of calculation of the value of the investment is NPV = Rp. 238 928 917, IRR = 64.48% and PBP = 2,050 years. Development of Toko DisneckMerchandise declared eligible for IRR value is greater than the value of MARR and the NPV is positive. Keywords: Feasibility Analysis, NPV, IRR, PBP, Disneck Merchandise store.